Case Report: The carney complex led to the tragic passing of a young girl in the prime of her life - Yun, Shurong; Liu, Xingquan; Wang, Yaxi; Liu, Zhiping; Wu, Jing; Duan, Shasha; Zhang, Xiaoshan; Shi, Yilu (Frontiers in Cardiovascular Medicine, 2025)
ObjectiveWe identified a novel mutation in the protein kinase cAMP-dependent type I regulatory subunit α (PRKAR1A) gene in a Chinese patient presenting with multiple recurrent cardiac myxomas, confirming a diagnosis of Carney complex (CNC). By reviewing the relevant literature, we aimed to enhance our understanding of this condition.Case presentationA 12-year-old girl was referred to the Department of Cardiac Surgery at our hospital due to multiple cardiac myxomas. She had previously undergone two surgical resections of cardiac myxoma, both of which recurred shortly after the procedures. Physical examination revealed a blood pressure of 118/76 mmHg, body weight of 43 kg, height of 158 cm, and body mass index of 17.2 kg/m². No obvious skin pigmentation or nevi were observed. Whole-exome sequencing revealed a mutation in PRKAR1A (c.329dupC: p. A110fs), and the patient was diagnosed with CNC. During follow-up, the child succumbed to heart failure.DiscussionCNC is a rare autosomal dominant endocrine neoplasia syndrome, with approximately 53% of affected individuals having a history of cardiac myxoma. This condition should be suspected in patients initially diagnosed with multiple cardiac myxomas. Early diagnosis and treatment through multidisciplinary cooperation can improve prognosis.